the role of senior management commitment to total quality in the implementation of knowledge management processes_Asurvey of asample of civil colleges - اللامي, غسان قاسم; سعيد, هدى قاسم (Journal of Economics and Administrative Sciences, 2014)
Occupies total quality management applications play a key role in the development of institutions of higher education performance and achieve its strategic objectives through the commitment of senior management and their employees to continuous improvement of the quality of performance in the various areas of work, and can be integrated knowledge management processes, which means identifying information of value and how to take advantage. The data were collected using the style of the questionnaire for the purpose of analyzing their results on a sample composed of 83 member of the administrative leadership in colleges as representing the decision-making centers in those colleges .      The research to a set of conclusions, mainly there a correlation between the commitment of senior management and operations of knowledge management, which emphasizes the role of senior management in the success of the application of knowledge management in colleges by allocating adequate resources and selection of human resources required and customizations financial and technological support for the implementation of knowledge management. Focused recommendations the continued support by senior management for their essential role in the creation and maintenance of a knowledge management environment and thus support the conversion to intensive efforts contribute to the success of knowledge management